A critical review of popular technological solutions for climate change as evident in the movie industry - Shanthini, Rajaratnam (National Science Foundation: Colombo, 2016)
This paper critically reviews four selected movies dealing with climate change and the resulting ecosystem deterioration, namely, The Day After Tomorrow, An Inconvenient Truth, The 11th Hour and The Age of Stupid. It scrutinises the limitations, the hypocrisy and the dilemma embedded in the technological solutions to climate change suggested in the movies, such as reduction in fossil fuel consumption, use of energy efficient technologies and adaptation of renewable energy. The movies’ failure to discuss crucial phenomena such as the ‘rebound effect’ of efficiency improvement technologies, ‘well-to-wheel life cycle assessment’ of renewable energy technologies, and their power to reverse the capability of chosen technological solutions to combat ecosystem deterioration are highlighted. The review also stresses on the need for movies to place emphasis on moving away not only from egocentrism, as illustrated by reference to selected footages from the movie Amélie, but also from human-centrism towards eco-centrism to save the ecosystem on which all lives depend upon.
Keywords: Amélie; An inconvenient Truth; Climate change; Energy efficiency; Global warming; Lifecycle assessment; Movie; Rebound effect; Renewable energy; The 11th Hour; The Age of Stupid; The Day After Tomorrow